EMPIRICAL EVIDENCES FROM A COFFEE PARADOX: AN EXPORT SUPPLY/PRICE ASYMMETRY APPROACH - P. Lynn Kennedy (한국농촌경제연구원, 2009)
This paper aims to determine the solidity of the notion of the "coffee paradox" using annual data from 1977 to 2007. In the confines of an export supply model, we analyze the effects of export coffee price on export volume. Price and profit equation are used to determine the effects of market power on export coffee price and measure changes in the retail and export price. We also estimate the elasticity of transmission and price asymmetry as a means of verifying the "coffee paradox." Ordinary Least Square (OLS), Instrumental Variables (IV), and simultaneous equation with Seemingly Unrelated Regressions (SUR) methods of econometric analysis are employed. Empirical results suggest that the world coffee market is characterized by "coffee paradox" due to different changes between retail and export prices of coffee, and that it is the existence of market power in importing countries that is the main contributor to the condition of price asymmetry.
Keywords: export supply model; coffee paradox; elasticity of transmission; price asymmetry; price equation; profit equation